0431 Bedtime Social Technology Use (Partner and Self) Related to Daytime Sleepiness and Sleep. (12th April 2019) - Mastin, David F; Jackson, Daphne; Smith, Quinshell; Watson, Shanieke; Diederich, Haylie; Moore, Bruce; Peszka, Jennifer
Abstract: Introduction: One third of Americans report bedpartner sleep problems negatively impact their sleep. Previously we found one third of participants reported passive bedpartner social technology use related to disrupted sleep and increased sleepiness. We examined the relationship of both passive and active bedpartner social technology use and one's own passive and active social technology use with daytime sleepiness and sleep. Active social technology use was defined as initiating use during bed time, passive social technology use was defined as the potential for sleep interruption by social technology without user action. Methods: 199 university students (age: M=20.5 years, SD=6.45) recruited from introductory psychology courses were given extra credit for participation. Participants completed demographic information, the Epworth Sleepiness Scale (ESS), the Pittsburg Sleep Quality Index, questions regarding associated features of inadequate sleep hygiene, and the Sleep Hygiene Index. Four additional questions assessed frequency of active and passive social technology use and being aware of bedpartner active and passive social technology use during sleep time. For self and bedpartner, active and passive technology use were analyzed separately and combined. Results: Self: 60.3% and 62.3% of students reported frequently or always using active and passive bedtime social technology, respectively. More frequent use was significantly related to greater daytime sleepiness (ESS) (r(196)=.142, p<.05), sleep disturbance (r(190)=.189, p<.05), and associated features of inadequate sleep hygiene (daytime sleepiness (r(196)=.176, p<.05), mood disturbance (r(197)=.174, p<.05), avolition (r(196)=.149, p<.05), and reduced cognition (r(197)=.177, p<.05)). Bedpartner: 20.7% and 26.1% of students reported frequently or always noticing their partner's active and passive use, respectively. Awareness of bedpartner active or passive social technology use was not significantly related to any sleep/sleepiness variables. Conclusion: Participants were frequent users of bedtime social technology which was related to daytime sleepiness, disrupted sleep, and related complaints. Less than a third of participants were aware of partner active and passive bedtime social technology and surprisingly no sleep related associations were found. Future research should separate participants with no bedpartner from those who are unaware of their bedpartner's social technology use. Support (If Any): none